Ellipsometric control of quality of polished MgF₂ optical ceramics - Maslov, V.P.; Sarsembaeva, A.Z.; Sizov, F.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
In this work, ellipsometric measurements were used to optimise the technology of machine working the polished parts made of MgF₂ optical ceramics. The ellipsometry is a high-performance contactless method to control quality of optical surfaces, which is used here due to a sharp response of light polarisation conditions to the properties and parameters of surface and subsurface layers in investigated reflective systems. It is shown that the highly productive technology of diamond polishing provides achievement of ellipsometric parameters at a level of conventional methods of polishing.